The Correlation of initial hematological feature with advanced stage in Chronic Lymphocytic Leukemia in Kurdistan Region of Iraq - Tavan Ismael Mahmood (Zanco Journal of Pure and Applied Sciences, 2021)
Chronic lymphocytic leukemia (CLL) is considered by an accumulation of matured lymphocytes in the blood, bone marrow, spleen. And lymph .We aimed to find the correlation of initial hematological feature with advanced stage in CLL. Methods: A retrospective study was conducted on 138 patients with CLL, confirmed by flow cytometry of peripheral blood collected in Hiwa Hematological and Oncological Hospital in Sulaimani, Nanakaly Hospital in Hawler, and Azadi Hematology - Oncology Center in Duhok, Kurdistan Region of Iraq dated from January 1, 2010, to December 31, 2020. Results: The mean age of 63.07±11 years with male predominance. The majority of patients at presentation were Rai Stage II and Binet stage A. The frequency of DAT positivity was found in (6.5%), which also established appositive relationship with advanced stage, there were statistically significant relation of hemoglobin level, platelet counts, LDH level to Rai stage and Binet stage disease (P value <0.001), No association were noted between different age groups and initial laboratory finding, also no relation of gender to staging. Conclusion: In the present study there was a significant relation between laboratory findings (hemoglobin, platelet count, LDH levels) to with staging, in addition DAT positivity demonstrated a significant correlation with advanced stage, those with High LDH levels associated with more advanced Rai stage.